A nation of empire : the Ottoman legacy of Turkish modernity - Meeker, Michael E. (University of California Press, 2002)
This innovative study of modern Turkey is the result of many years of ethnographic fieldwork and archival research. Michael Meeker combines anthropological and historical methods to examine the transition from the Ottoman Empire to the Turkish Republic in a major region of the country, the eastern Black Sea Coast.